Archaeology Argot: Rhyton (Biblical archaeology review, 2023)
The article discusses the historical significance and use of rhyta, unique conical drinking horns with spouts, tracing their origins in prehistoric Eurasia, notably Crete, and their popularity in Persia for feasts and religious ceremonies, featuring examples made from various materials.